2012
DOI: 10.1111/j.1742-4658.2012.08694.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulated long non‐coding RNA H19 contributes to proliferation of gastric cancer cells

Abstract: Long non-coding RNAs (lncRNAs) have been shown to have important regulatory roles in cancer biology, and the lncRNA H19 is up-regulated in hypoxic stress and in some tumors. However, the contributions of H19 to gastric cancer remain largely unknown. In this study, we assayed the H19 expression level in gastric cancer tissues by real-time PCR, and defined the biological functions by flow cytometry and RNA immunoprecipitation. We demonstrated that H19 levels were markedly increased in gastric cancer cells and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
306
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(315 citation statements)
references
References 28 publications
8
306
0
1
Order By: Relevance
“…18 Increased expression of H19 has been observed in some cancers, such as gastric 25,30 and bladder cancer, 16 and decreased expression in others, such as HCC, 13 suggesting that H19 involves either oncogenic or tumor suppressor properties. Hao et al 10 introduced a construct expressing the H19 gene into the kidney tumor cells and observed that overexpression of H19 induced a slower growth rate, a much lower anchorage-independent growth rate in soft agar, and no tumor formation in mice, which indicate the tumor suppressor properties of H19 in kidney tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Increased expression of H19 has been observed in some cancers, such as gastric 25,30 and bladder cancer, 16 and decreased expression in others, such as HCC, 13 suggesting that H19 involves either oncogenic or tumor suppressor properties. Hao et al 10 introduced a construct expressing the H19 gene into the kidney tumor cells and observed that overexpression of H19 induced a slower growth rate, a much lower anchorage-independent growth rate in soft agar, and no tumor formation in mice, which indicate the tumor suppressor properties of H19 in kidney tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of H19 has been observed in some cancers, such as gastric 25,30 and bladder cancer, 16 and decreased expression in others, such as hepatocellular carcinoma (HCC), 13 suggesting that H19 may have either oncogenic or tumor suppressor properties, although the exact mechanism is still elusive. 11 A previous study showed that c-Myc (Myc) significantly induces the expression of H19 in diverse cell types, including breast epithelial, glioblastoma, and fibroblast cells, suggesting that H19 may play an important role in glioblastoma development.…”
mentioning
confidence: 99%
“…H19 is a member of a highly-conserved cluster of imprinted genes, and was the first lncRNA to be associated with cancer (12). Previous studies have indicated that H19 exhibits dysregulated expression in GC (13,14), hepatocellular carcinoma (15), bladder cancer (16), breast cancer (17) and esophageal cancer (18), and that itmay cause tumor promoting and suppressing effects (19). Niu et al (20) screened lncRNA expression profilesfrom colorectal cancer and adenoma samples, and identified a novel lncRNA, AK027294, which was associated with cell proliferation, migration and apoptosis in colorectal cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, lncRNA was thought to be 'junk nucleotides', but recent evidence indicates that lncRNA is as important in epigenetic modulation as miRNA (74). Aberrant expression of certain types of lncRNA has been associated with poorer prognosis in breast cancer (75), hepatocellular carcinoma (76) and lung carcinoma (77); and it has recently been demonstrated to possess clinical significance in GC (78)(79)(80)(81)(82)(83)(84)(85) (Table III). lncRNA in plasma is reportedly detectable in patients with GC, as with miRNA (86).…”
Section: Long Non-coding Rna (Lncrna)mentioning
confidence: 99%